Analytical methods for agricultural contaminants - Maestroni, Britt M.; Ochoa, Victoria; Cannavan, Andrew (Academic Press, 2019)
Analytical Methods for Agricultural Contaminants provides proven laboratory practices and methods necessary to control contaminants and residues in food and water. This reference provides insight into good laboratory practices and examples of methods used in individual specialist laboratories, thus enabling stakeholders in the agri-food industry to appreciate the importance of proven, reliable data and the associated quality assurance approaches for end product testing for toxic levels of contaminants and contaminant residues in food. The book offers standard operating procedures and tools for researchers, practitioners and students to confidently engage in using research methods with the aim to control contaminants. Users in a laboratory setting will find this to be a practical and useful reference on how to detect and control agricultural contaminants for a safe food supply.